2011
DOI: 10.1038/hr.2011.9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of global DNA methylation and paternally imprinted H19 gene methylation in preeclamptic placentas

Abstract: Preeclampsia (PE) is a severe hypertensive disorder associated with pregnancy; despite substantial research effort in the past several years, the etiology of PE is still unclear. The role of epigenetic factors in the etiology of PE, including DNA methylation, has been poorly characterized. In the present study, we investigated global DNA methylation as well as DNA methylation of the paternally imprinted H19 gene in preeclamptic placentas. Using 5-methylcytosine immunohistochemistry and Alu and LINE-1 repeat py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 51 publications
3
59
0
1
Order By: Relevance
“…The JEG-3 cells were transfected with miR-675 mimics together with Nodalexpressing construct or pCDNA4 plasmid vector. Similar as our previous report, 23 we consistently observed Smad2 activation and growth inhibition in cells transfected with Nodal-expressing plasmid. As shown in Figure 3C and D, co-transfection of miR-675 mimics could substantially facilitate the Nodal effects on Smad2 phosphorylation and cell proliferation in JEG-3 cells.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The JEG-3 cells were transfected with miR-675 mimics together with Nodalexpressing construct or pCDNA4 plasmid vector. Similar as our previous report, 23 we consistently observed Smad2 activation and growth inhibition in cells transfected with Nodal-expressing plasmid. As shown in Figure 3C and D, co-transfection of miR-675 mimics could substantially facilitate the Nodal effects on Smad2 phosphorylation and cell proliferation in JEG-3 cells.…”
Section: Resultssupporting
confidence: 80%
“…21,22 We previously reported that PE placentas exhibited lower mRNA expression and hypermethylation in promoter region of H19 gene compared with normal placentas. 23 In the present study, we attempt to reveal the role of H19 gene in human . The levels of h19 and miR-675 were separately adjusted by that of GApDh and U6, and the relative value to corresponding Nc was presented as Mean ± seM according to three independent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Kulkarni et al (31) measured the global DNA methylation level in placentas of women with PE using the Methylamp TM Global DNA methylation quantification kit. Using 5-methylcytosine immunohistochemistry and Alu and LINE-1 repeat pyrosequencing, Gao et al (32) investigated global DNA methylation as well as DNA methylation of the paternally imprinted H19 gene in preeclamptic placentas. There is relatively little concordance between our findings and these other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Az egyébként tumorszuppresszor hatású H19-gén fokozott expressziója humán embrionális szövetekben észlelhető; a szöveti növekedés és fejlődés regulációján túl -Yu és munkatársai vizsgálati eredményei alapján -részt vesznek a praeeclampsia patofi ziológiai folyamataiban [58]. Gao és munkatársai ugyanezen gén promoter régiójának fokozott metilációját tapasztalták praeeclampsiában, míg más vizsgálatok e terület hipometiláció-ját igazolták méhen belüli növekedési retardáció esetén [59,60]. E szempontból a CUL7-gén metilációs mintázatának alakulása praeeclampsia és IUGR esetén hasonló a H19 kapcsán tapasztalhatókhoz.…”
Section: öSszefoglaló Közleményunclassified